2017
DOI: 10.1093/biolre/iox053
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against cisplatin-induced ovarian damage in mice via the MT1 receptor and antioxidant activity†

Abstract: This study evaluated the receptor- and/or antioxidant stress-mediated mechanisms by which melatonin prevents the ovarian toxicity of cisplatin treatment. The expression of the MT1 receptor in mouse ovaries was investigated by immunohistochemistry. Pretreatment with melatonin (5, 10, or 20 mg/kg body weight, i.p.) before cisplatin (5 mg/kg body weight, i.p.) was administered to mice once daily for 3 days (phase I). The pharmacological modulation via melatonin type 1 and/or 2 receptors was analyzed by administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 54 publications
1
72
3
Order By: Relevance
“…In mice, the melatonin treatment can protect ovary from cisplatin-induced damage depends on both its antioxidant capacity and MT1 receptor mediating signal pathway. 60 In current research, melatonin treatment improved the expression of MT1 receptor, AMPK and p-AMPK. This indicates that MT1 may mediate the protective effects of melatonin on female's fertility.…”
Section: Discussionmentioning
confidence: 76%
“…In mice, the melatonin treatment can protect ovary from cisplatin-induced damage depends on both its antioxidant capacity and MT1 receptor mediating signal pathway. 60 In current research, melatonin treatment improved the expression of MT1 receptor, AMPK and p-AMPK. This indicates that MT1 may mediate the protective effects of melatonin on female's fertility.…”
Section: Discussionmentioning
confidence: 76%
“…Terminal deoxynucleotidyl transferase (TdT)‐mediated dUTP nick‐end labeling (TUNEL) and PCNA analyses were performed in the fresh control and in treatments that showed the best results for normal follicles as previously described (Barberino et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of PCNA was performed according to Barberino et al (2017). The sections were mounted in Starfrost slides (Knittel) and incubated in citrate buffer (Dinâmica) at 95°C in a deckloaking chamber (Biocare) for 40 min.…”
Section: Pcna Immunohistochemistrymentioning
confidence: 99%
“…In general, melatonin is considered a classic antioxidant molecule. Most studies on the new medicinal uses and mechanisms of melatonin have found that melatonin can play an antioxidant role through the following two pathways: receptor-dependent signal transduction pathway to activate the antioxidant system [30,31]; Or nonreceptordependent mechanism as the antioxidant substrates directly neutralize oxidants [32].…”
Section: Discussionmentioning
confidence: 99%